2016
DOI: 10.1089/acm.2015.0349
|View full text |Cite
|
Sign up to set email alerts
|

Aroma Effects on Physiologic and Cognitive Function Following Acute Stress: A Mechanism Investigation

Abstract: Objective: Aromas may improve physiologic and cognitive function after stress, but associated mechanisms remain unknown. This study evaluated the effects of lavender aroma, which is commonly used for stress reduction, on physiologic and cognitive functions. The contribution of pharmacologic, hedonic, and expectancyrelated mechanisms of the aromatherapy effects was evaluated. Methods: Ninety-two healthy adults (mean age, 58.0 years; 79.3% women) were randomly assigned to three aroma groups (lavender, perceptibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 30 publications
(24 reference statements)
0
42
0
2
Order By: Relevance
“…None of the participants presented with any abnormality in terms of their physical, mental, or olfactory health or were currently using prescription drugs or were current smokers. While the purpose and schedule of the experiments were explained to the participants, the effects of the wood used in our experiments were not discussed to avoid the influence of individual expectations on the results [ 23 , 24 ]. Written informed consent was obtained from all participants prior to study initiation.…”
Section: Methodsmentioning
confidence: 99%
“…None of the participants presented with any abnormality in terms of their physical, mental, or olfactory health or were currently using prescription drugs or were current smokers. While the purpose and schedule of the experiments were explained to the participants, the effects of the wood used in our experiments were not discussed to avoid the influence of individual expectations on the results [ 23 , 24 ]. Written informed consent was obtained from all participants prior to study initiation.…”
Section: Methodsmentioning
confidence: 99%
“…The respirations remained consistent with the placebo (water) group. Working memory testing revealed a 15% increase in scores for working memory with the lavender over the other groups [13]. The study concluded there was a positive correlation between lavender and working memory and a decrease in stress related physiological findings with both aromas in comparison to the placebo group.…”
Section: Critique Of Articlesmentioning
confidence: 76%
“…Ninety-two individuals were randomly selected and placed into three aromatherapy groups which included lavender, a coconut, and a placebo (water) group. Cognitive and physical assessments were performed both before (for baseline) and after exposure to a stress battery [13]. Inclusion criteria included ages 50-85, no current medications and nonsmokers.…”
Section: Critique Of Articlesmentioning
confidence: 99%
“…Volatile molecules are ubiquitous in our environment and have shown to be the active principle of many medicinal plants commonly used in phytotherapy. In addition, they may improve well‐being and work efficiency . Nevertheless, knowledge about their influence on the human organism is still very limited.…”
Section: Introductionmentioning
confidence: 99%